FIDIC quick reference guide. - Barr, Brian; Grutters, Leo (ICE Publishing, 2015)
This reference guide provides a valuable tool for practitioners who are either preparing or using the contract form, as it directs the user through this minefield of directly, or often implied, cross-referenced sub-clauses.